(untitled) (Educational Dimension, 2021)
The aim of the article is to disclose the requirements for the content and training of PhDs in the specialty 151 Automation and computer-integrated technologies, the implementation of which will contribute to the successful accreditation of educational and scientific programs of other specialties of higher educational institutions in Ukraine. Research Methods: The study involved the analysis of the regulatory framework of documents for the training of doctors of philosophy, standards of higher education, scientific and methodological literature, educational and scientific programs of higher educational institutions. The results of the study consist in highlighting the main aspects that should be taken into account for the successful accreditation of educational and scientific programs.